The flight of capital from developing countries - Susanne Erbe (Intereconomics, 1985)
The export of capital, legally and illegally, is a major problem for many developing countries. The following study analyses the causes and nature of the flight of capital and estimates its scale in 34 countries.
Keywords: 330; Debt Problems